2012
DOI: 10.1364/oe.20.009249
|View full text |Cite
|
Sign up to set email alerts
|

Designing coupled-resonator optical waveguides based on high-Q tapered grating-defect resonators

Abstract: Abstract:We present a systematic design of coupled-resonator optical waveguides (CROWs) based on high-Q tapered grating-defect resonators. The formalism is based on coupled-mode theory where forward and backward waveguide modes are coupled by the grating. Although applied to strong gratings (periodic air holes in single-mode silicon-on-insulator waveguides), coupled-mode theory is shown to be valid, since the spatial Fourier transform of the resonant mode is engineered to minimize the coupling to radiation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…Это может быть вызвано тем, что брэггов-ская частота фотонно-кристаллического волновода не совпадает с резонансной частотой. В этом случае, чтобы реализовать условие θ = π/2, требуется доба-вить фрагмент волновода между резонаторами [9].…”
Section: таблunclassified
“…Это может быть вызвано тем, что брэггов-ская частота фотонно-кристаллического волновода не совпадает с резонансной частотой. В этом случае, чтобы реализовать условие θ = π/2, требуется доба-вить фрагмент волновода между резонаторами [9].…”
Section: таблunclassified
“…The coupling value between resonators in the array is determined by reg n , the number of holes with the maximum radius between defects. It can be shown [16] that for two adjacent resonators with quality factors Q 1 and Q 2, the coupling coefficient is…”
Section: Example Of Integrator Based On Pc Nanobeam Cavitymentioning
confidence: 99%
“…Therefore, the width of the spectral peaks determines the cavity losses by scattering. In [16,17], it is proposed that a resonant mode can be formed with an envelope matching the Gaussian function. One of the same papers [17] showed that a resonant mode with a Gaussian envelope can be realized by changing the PC nanobeam material fill factor quadratically.…”
Section: Example Of Integrator Based On Pc Nanobeam Cavitymentioning
confidence: 99%
“…To further decrease τ and to not violate the weak interaction condition, one can use arrays of resonators. A similar procedure was applied to optical delay lines based on photonic crystal (PhC) coupled cavities in order to optimize the dispersion characteristics [8]. The same approach of using resonators arrays can be applied to the design of the resonator for a specific nth order differentiation.…”
mentioning
confidence: 99%